Stewart Hensley papers - Hensley, Stewart, 1913-1976.
Correspondence, notebooks, transcriptions of interviews with officials in the U.S. Dept. of State and other government agencies, speeches, research files, printed matter, and other papers relating to Hensley's career as a reporter and chief diplomatic correspondent for the United Press Associations (later United Press International). Correspondents include Zbigniew Brzezinski, Dean Rusk, and Ronald L. Ziegler.
Library of Congress Prints and Photographs Division.
Newspaper correspondent.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brzezinski, Zbigniew, -- 1928- -- Correspondence; Rusk, Dean, -- 1909-1994 -- Correspondence; Ziegler, Ronald L. -- 1939-2003 -- Correspondence; United States. -- Department of State -- Officials and employees -- Interviews; United Press Associations; United Press International; Journalism; United States -- Foreign relations -- 20th century; United States -- Officials and employees -- Interviews; Journalists